Effects of free trade agreements on global value chain trade----a research perspective of GVC backward linkage. Issue 44 (20th September 2021) - Zhang, Runqi; Zhao, Jinlong; Zhao, Jingyuan
ABSTRACT: Using the World Input-Output Database from 2000 to 2014 combined with the Database from the World Bank, this paper examines the export promotion effects of FTAs on member countries' GVC trade. Empirical analysis shows that, first, the depth of free trade agreements has significant positive effects on both the total trade and exports of foreign value added (FVA) among member countries. Each additional core clause in free trade agreement will increase the FVA exports by 0.27%. Second, free trade agreements not only enhance the export levels of simple value chains and complex value chains but promote the value-added exports of all sub-items of GVC trade at different levels. Further study shows that gaps in economic development levels among FTA members and FTA structures can both lead to asymmetric and heterogeneous effects on their FVA exports. Moreover, as to FTA contents, WTO-X clauses which focus more on trade policy coordination behind the border have more important impacts on FTA members' FVA exports.